Pengaruh Waktu Emaskulasi terhadap Keberhasilan Persilangan Beras Hitam X Beras Putih dan Evaluasi Karakter Agronomi Tetua Persilangan - Mirnawati Mirnawati; Muhammad Syafi’i; Rommy Andhika Laksono; Heni Safitri; Puji Lestari (Jurnal Ilmiah Wahana Pendidikan, 2022)
Emasculation is removing male sex (stament) from the female parental to avoid self pollinated. The purpose of this research to determine the effect of differences time emasculation to success crosses of black rice x white rice and agronomic character of the crosses parental.This research was conducted at IP2TP Muara, Bogor. The method used was Completely Randomized Design (CRD) with combination factors, the emasculation time factor consist of 2 levels and crosses factor consist of 8 levels, and Randomized Block Design (RBD) with single factor, parental varieties factor (T) consist of 6 levels, repeated 3 time, there are 48 and 18 experimental units with single cross method. Analysis data result used ANOVA test and further testing with DMRT 5% levels. The result of research showed that the diffences time emasculation which combinated with crossing set had significant effect to crosses success percentage. Differences parental varieties of crosses had a significant effect to plant height, flowering age, physiological mature age, fill grain, empty grain, and 1000 grain weight, but not significant to numbers of tillers. The best result is e₁s₅ treatment (Setail/Sintanur emasculation time 08:00-10:00 am).